Osteogenic Differentiation from Embryonic Stem Cells - Yu, Yanhong; Pilquil, Carlos; Opas, Michal (Methods in molecular biology (Clifton, N.J.), 2016)
Embryonic stem (ES) cells have been widely studied due to their pluripotency and their potential of self-renewal. Murine ES cells are useful in investigating the molecular pathways underlying their differentiation to various mature cell types in the body. This chapter describes the maintenance of murine ES cells in culture and a routine ES cell osteogenic differentiation protocol utilized in our laboratory.